The anti-tumor effect of proteasome inhibitor MG132 for human adenoid cystic carcinoma: correlate with the emerging role of Nrf2/Keap1 signaling pathway - Jiazhi Xu; Haiwei Wu; Jiatong Sun; Zhiyuan Gong; Xiaoya Lu; Enli Yang; Zhanwei Chen; Shengyun Huang; Xiaolin Nong; Dongsheng Zhang (Head & Face Medicine, 2022)
Abstract Background Adenoid cystic carcinoma (ACC) is one of the most common malignant salivary gland tumors. Moreover, the unique biological characteristics and complex structures of ACC contribute to its poor survival rates. Recently, proteasome inhibitors have been shown to elicit satisfactory therapeutic effects in the treatment of certain solid tumors, but few studies have been implemented to investigate the effects of proteasome inhibitor therapy for ACC. Methods In this present study, cell counting kit-8 assay and flow cytometry assay were performed to examine the effects of proteasome inhibitor (MG132) on cell viability and apoptosis. We applied western blot and immunofluorescence staining to explore the expression of the Nrf2/Keap1 signaling pathway and P62, additionally Nrf2 inhibitor (ML385) was utilized to evaluate the role of Nrf2/Keap1 signaling pathway in MG132-induced cell apoptosis. Results Our data indicated that MG132 significantly suppressed the growth of ACC-83 cells(MG132 10µM P = 0.0046; 40µM P = 0.0033; 70µM P = 0.0007 versus control) and induced apoptosis (MG132 10µM P = 0.0458; 40µM P = 0.0018; 70µM P = 0.0087 versus control). The application of MG132 induced the up-regulation of Nrf2/Keap1 signaling pathway. Furthermore, inhibition of Nrf2 attenuated the therapeutic effects of MG132 for ACC (both ML385 + MG132 10µM P = 0.0013; 40µM P = 0.0057; 70µM P = 0.0003 versus MG132). P < 0.05 was considered statistically significant. Conclusions Our results revealed that proteasome inhibitors MG132 could inhibit the cell viability and induce the apoptosis of ACC through Nrf2/Keap1 signaling pathway.